POLA PENANGANAN PERILAKU BULLYING PADA SEKOLAH DASAR - Zulkifli Mansyur (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACTThis study aims to look at bullying behavior that occurs in elementary schools and how the pattern of handling it by the parties involved in it. This study uses a descriptive quantitative approach. Each variable uses a measuring instrument in the form of a scale made for each variable. The age level and background of the subject will also be the limitations that will be carried out in taking information. This study involved 75 students who were sampled from grades 4 to 6. Bullying behavior that occurred in elementary schools was still dominated by physical bullying (48.56%), followed by verbal bullying (26.28%), ostracism (12.10%), cyberbullying (5.2%), and sexual harassment (7.05%). Bullying behavior is only considered normal delinquent behavior so that no serious action is taken by the school, especially teachers so that there is no specific handling of bullyingKeywords: Bullying, Elementary schoolÂ Â ABSTRAKPenelitian ini bertujuan untuk melihat perilaku bullying yang terjadi di sekolah dasar dan bagaimana pola penanganannya oleh pihak yang terkait didalamnya. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Masing-masing variabel menggunakan alat ukur berupa skala yang dibuat untuk masing-masing variabel. Tingkatan umur dan latar belakang subjek juga akan menjadi batasan-batasan yang akan dilakukan dalam pengambilan keterangan. Penelitian ini melibatkan 75 orang siswa yang di ambil sampel dari kelas 4 sampai 6. Perilaku perundungan yang terjadi pada sekolah dasar masih di dominasi oleh perundungan fisik (48,56%), kemudian di ikuti perundungan verbal (26,28%), tindakan pengucilan (12,10%), perundungan di dunia maya (5,2%) dan penindasan seksual (7,05%). Perilaku perundungan hanya di anggap perilaku kenakalan biasa saja sehingga tidak ada tindakan serius yang di ambil oleh pihak sekolah khususnya guru sehingga tidak ada penanganan yang spesifik tentang perundunganKata Kunci : Bullying, Sekolah dasar